2010
DOI: 10.3109/03008207.2010.511353
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural mapping of collagen fibril interactions

Abstract: The fibrous collagens form the structural basis of all mammalian connective tissues, including the vasculature, dermis, bones, tendons, cartilage, and those tissues that support organs such as the heart, kidneys, liver, and lungs. The helical structure of collagen has been extensively studied but in addition to its helical character, its molecular packing arrangement (in its aggregated or fibrillar form) and the presence of specific amino acid sequences govern collagen's in vivo functions. Collagen's molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(173 citation statements)
references
References 117 publications
4
166
0
2
Order By: Relevance
“…This, together with the study of the interaction of collagen fibrils with other relevant biomolecules such as proteoglycans, will provide critical details for the understanding of structure-property relationships in the broader class of collagen materials, and at larger hierarchical scales. Indeed, important experimental crystallography [57,58] efforts are ongoing to elucidate the structure of collagen fibril-proteoglycan complexes. Other challenges remain with respect to the greater level of disorder that is expected to be found in collagen fibrils, as outlined in [59].…”
Section: Resultsmentioning
confidence: 99%
“…This, together with the study of the interaction of collagen fibrils with other relevant biomolecules such as proteoglycans, will provide critical details for the understanding of structure-property relationships in the broader class of collagen materials, and at larger hierarchical scales. Indeed, important experimental crystallography [57,58] efforts are ongoing to elucidate the structure of collagen fibril-proteoglycan complexes. Other challenges remain with respect to the greater level of disorder that is expected to be found in collagen fibrils, as outlined in [59].…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been shown that traction forces exerted by cells on the ECM expose cryptic domains within collagen and fibronectin that can stimulate intracellular signaling pathways affecting cellular growth and ECM turnover (Hocking & Kowalski, 2002; Vogel & Sheetz, 2009; Orgel et al ., 2011; Bonnans et al ., 2014). The actin myosin cytoskeleton is the primary source of force generation by cells.…”
Section: Discussionmentioning
confidence: 99%
“…2) identified along the Îą1(I) chain 36 are particularly important for matrix quality. The C terminal MLBR3 is especially crucial for interactions of collagen with extracellular matrix pro teins; substitutions in this domain impair extracellular matrix organization and have predominantly lethal out comes 36,37 . Mutations in the C propeptide that impair Îą chain recognition are responsible for ER associated protein degradation activation, which favours the removal of unassembled chains 29 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Mutations in the C propeptide that impair Îą chain recognition are responsible for ER associated protein degradation activation, which favours the removal of unassembled chains 29 . In the Îą2(I) chain, lethal regions that align with proteoglycan binding sites on collagen fibrils have been identified along the chain; mutations in these domains may severely affect proper matrix assembly 36,37 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%